Arbitrary and Parallel Nanofabrication of 3D Metal Structures with Polymer Brush Resists. Issue 45 (6th October 2015) - Chen, Chaojian; Xie, Zhuang; Wei, Xiaoling; Zheng, Zijian
Abstract : 3D polymer brushes are reported for the first time as ideal resists for the alignment‐free nanofabrication of complex 3D metal structures with sub‐100 nm lateral resolution and sub‐10 nm vertical resolution. Since 3D polymer brushes can be serially fabricated in parallel, this method is effective to generate arbitrary 3D metal structures over a large area at a high throughput.